Changes in the quality and inequalities of work in Britain: New measures and emerging trends - Felstead, Alan (The Greek Review of Social Research, 2011)
This article outlines new approaches to, and measures of, the quality of work. These have been used in surveys of workers carried out in Britain over the last twenty years. These surveys have measured the skills workers use at work, the discretion and autonomy they enjoy, the effort levels they expend, and the extent to which they are committed to employment in general and the organizations for which they work in particular. Using data from around 22.500 workers, the article examines how age, gender and regional inequalities in the quality of work have changed over the last two decades.